Educational Autonomy and Islamic Education in Indonesia: Opportunities, Challenges, and Implications for Educational Quality - Najmi, Via Novelia; Nurhidayati Nurhidayati (Bulletin of Indonesian Islamic Studies, 2025)
Educational autonomy in Indonesia constitutes a strategic milestone in post-1998 educational reform, marked by a transition from a centralized to a decentralized system. This policy reflects the government’s commitment to promoting independence, participation, and accountability in educational governance at both regional and institutional levels. This study aims to examine the concept and implementation of educational autonomy while identifying the opportunities and challenges faced by Islamic educational institutions. Employing a qualitative-descriptive approach through library research, the study draws on regulatory and scholarly sources, including legislation, ministerial regulations, and recent academic literature. The findings reveal that educational autonomy provides substantial opportunities for Islamic educational institutions to foster curriculum innovation, strengthen community-based governance, and enhance educational quality in alignment with Islamic values. However, its implementation encounters significant challenges, including regional disparities in capacity, limited human resources, and weak coordination between local governments and the Ministry of Religious Affairs. The study concludes that the effectiveness of educational autonomy depends on stakeholder collaboration and institutional readiness to implement autonomy principles in a sustainable manner. This study contributes a policy-oriented framework that positions Islamic educational institutions as active actors in decentralized educational governance.